Two examples illustrated by Shane Baggs showing where the correction occurs.

The cube root of 27 is 3.
1. 1 | 1 | 27
2. 1 | 1 | 26
3. 2 | 1 | 26
4. 2 | 3 | 26
5. 4 | 3 | 26
6. 4 | 7 | 26
7. 4 | 7 | 19
8. 6 | 7 | 19 <=== Typo in the instructions occurs here
In step 8, instead of adding 2 as instructed in paragraph (f), add 1 as instructed in paragraph (e).
8. 5 | 7 | 19
9. 5 | 12 | 19
Now we add 2.
10. 7 | 12 | 19
11. 7 | 19 | 19
12. 7 | 19 | 0
It comes out even. Add 2 to the root number,
12. 7 + 2 = 9
and divide 9 by 3 to get 3, the answer.
13. 9 / 3 = 3


The cube root of 64 is 4.
1. 1 | 1 | 64
2. 1 | 1 | 63
3. 2 | 1 | 63
4. 2 | 3 | 63
5. 4 | 3 | 63
6. 4 | 7 | 63
7. 4 | 7 | 56
8. 6 | 7 | 56 <=== Typo in the instructions occurs here
In step 8 we should add 1, not 2.
8. 5 | 7 | 56
9. 5 | 12 | 56
Now add 2.
10. 7 | 19 | 56
11. 7 | 19 | 37
Now add 1.
12. 8 | 19 | 37
13. 8 | 27 | 37
Now add 2.
14. 10 | 27 | 37
15. 10 | 37 | 37
16. 10 | 37 | 0
17. 10 + 2 = 12
18. 12 / 3 = 4, which is the answer.

 

Back to cube roots

Abacus: Mystery of the Bead
Advanced Abacus Techniques

August, 2007